Practices and attitudes of bariatric surgeons in Israel during the first phase of the COVID-19 pandemic - Nahum Beglaibter; Orly Zelekha; Lital Keinan-Boker; Nasser Sakran; Ahmad Mahajna (BMC, 2020)
Abstract Introduction Israel ranks very high globally in performing bariatric surgery (BS) per capita. In the first phase of the COVID-19 pandemic the bariatric surgeons' community faced many concerns and challenges, especially in light of a decree issued by the Ministry of Health (MOH) on March 22nd, to ban all elective surgery in public hospitals. The aim of this study is to portray the practices and attitudes of Israeli bariatric surgeons in the first phase of the pandemic. Methods Anonymous web-based questionnaire sent to all active bariatric surgeons in Israel. Statistical analysis was performed using SAS software package. Results 53 out of 63 (84%) active surgeons responded to the survey. 18% practice in the public sector only, 4% in the private sector only and 78% in both sectors. 76% practice BS for more than 10 years and 68% perform more than 100 procedures a year. Almost all the surgeons (98%) experienced a tremendous decrease in operations. Nevertheless, there were substantial differences by sectors. In the public sector, 86% of the surgeons ceased to operate while 14% did not comply with the government's decree. In the public sector 69% of the surgeons were instructed by the administrators to stop operating. The majority of surgeons who continued to operate (77%) changed nothing in the indications or contra-indications for surgery. Among the surgeons who opted to refrain from operating on special sub-groups, the most frequent reasons were pulmonary disease (82%), age above 60 (64%), Ischemic heart disease (55%) and living in heavily affected communities. Roughly only half (57%) of the surgeons implemented changes in informed consent and operating room (OR) measures, contrary to guidelines and recommendations by leading professional societies. When asked about future conditions for reestablishing elective procedures, the reply frequencies were as follows: no special measures - 40%; PCR negativity - 27%; IgG positivity - 15%; waiting until the end of the pandemic- 9%. Conclusions We showed in this nation-wide survey that the variance between surgeons, regarding present and future reactions to the COVID-19 pandemic, is high. There were substantial differences between the private and the public sectors. Although the instructions given by the MOH for the public sector were quite clear, the compliance by surgeons and administrators was far from complete. The administrators in the public sector, but more so in the private sector were ambiguous in instructing staff, leading surgeons to a more "personal non-structured" practice in the first phase of the pandemic. These facts must be considered by regulators, administrators and surgeons when planning for reestablishing elective BS or in case a second wave of the pandemic is on its way.